Diastereoselective Radical Couplings Enable the Asymmetric Synthesis of anti‐β‐Amino‐α‐hydroxy Carboxylic Acid Derivatives. Issue 37 (8th October 2018) - Hidasová, Denisa; Janák, Martin; Jahn, Emanuela; Císařová, Ivana; Jones, Peter G.; Jahn, Ullrich
Abstract : anti ‐β‐Amino‐α‐(aminoxy) esters or amides are synthesized by merging polar asymmetric aza‐Michael additions of lithium 1‐phenylethylamides to α, β‐unsaturated carboxylic acid derivatives and diastereoselective radical couplings with the persistent free radical TEMPO mediated or catalyzed by ferrocenium hexafluorophosphate. Aliphatic α, β‐unsaturated carboxylic derivatives gave good to excellent anti ‐diastereoselectivity for the radical coupling step, whereas the selectivity remained lower for cinnamic acid derivatives. The method allows the convenient introduction of a protected oxygen functionality, which is stable to acidic, basic, hydride and hydrogenolytic reductive conditions, but can be deprotected with zinc and acetic acid in the presence of TBDMS and Boc groups without noticeable epimerization. The tandem aza‐Michael/oxygenation strategy was applied in total syntheses of the TH 2 cytokine secretion modulator cytoxazone, and dipeptide fragments of the anti ‐β‐amino‐α‐hydroxy acid containing macrocyclic peptides perthamide C and largamide H. Abstract : With a single jump anti ‐β‐amino‐α‐hydroxy esters or amides are obtained by merging polar aza‐Michael additions of chiral 1‐phenylethylamides to α, β‐unsaturated carboxylic acid derivatives and diastereoselective radical coupling with persistent free radical TEMPO.